Genomic Prediction of Genotypic Effects with Epistasis and Environment Interactions for Yield-Related Traits of Rapeseed (Brassica napus L.) - Luo, Xiang; Ding, Yi; Zhang, Linzhong; Yue, Yao; Snyder, John H.; Ma, Chaozhi; Zhu, Jun (Frontiers in Genetics, 2017)
Oilseed rape (Brassica napus) is an economically important oil crop, yet the genetic architecture of its complex traits remain largely unknown. Here, genome-wide association study was presented to dissect the genetic effects for eight yield-related traits, and the effects were partitioned into additive, dominance, epistasis, and environment interaction effects based on a mixed linear model approach. Additionally, the optimal genotype combination and the breeding value of superior line, superior hybrid and existing best line in mapping population were predicted for each trait in two environments based on the predicted genotypic effects. As a result, 17 quantitative trait SNPs (QTSs) with total heritability varied from 58.47% to 87.98% were identified to be significantly associated with target traits, and most of which were contributed by dominance, epistasis, and environment-specific effects. The results indicated that non-additive effects made large contributions to heritability and epistasis, and also noted that environment interactions were important variants for oilseed breeding. Our study facilitates the understanding of genetic basis of rapeseed yield trait, helps to accelerate rapeseed breading, and also offers a roadmap for precision plant breeding via marker-assisted selection.